Personality, time-of-day preference, and eating behavior: The mediational role of morning-eveningness. (April 2015) - Walker, Ryan J.; Christopher, Andrew N.; Wieth, Mareike B.; Buchanan, Joshua
Highlights: Conscientiousness, agreeableness, and extraversion predicted healthy eating behavior. Neuroticism predicted unhealthy eating behavior. Conscientiousness, agreeableness, and extraversion predicted morningness. Neuroticism predicted eveningness. Morning-eveningness mediated the relation between personality and eating behavior. Abstract: Although prior research has established that eating behaviors are related to both the Big Five personality traits and time-of-day preference, no research has directly examined if time-of-day preference mediates personality differences in eating behavior. We directly tested this model by assessing participants' ( N  = 279) Big Five personality traits, time-of-day preference, and three-factors of eating (i.e., restrained eating, uncontrolled eating, and emotional eating) using validated questionnaires. Mediation analyses revealed that time-of-day preference partially mediated the relationship between the personality factors (conscientiousness, neuroticism, and extraversion) and eating behavior, primarily uncontrolled eating. These results indicate that time-of-day preference, in part, accounts for personality differences in eating behavior. This emphasizes the need to assess time-of-day preference when examining the relationship between personality and health-related behaviors.